2023
DOI: 10.1038/s41598-023-33524-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of physicochemical features of carbon electrodes on the capacitive performance of supercapacitors: a machine learning approach

Abstract: Hybrid electric vehicles and portable electronic systems use supercapacitors for energy storage owing to their fast charging/discharging rates, long life cycle, and low maintenance. Specific capacitance is regarded as one of the most important performance-related characteristics of a supercapacitor’s electrode. In the current study, Machine Learning (ML) algorithms were used to determine the impact of various physicochemical properties of carbon-based materials on the capacitive performance of electric double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 67 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Consequently, there has been a shift in focus towards using ML models to forecast the effectiveness of SCs, considering the impact of doping materials as a percentage, as well as other structural and operational characteristics. Mishra et al [101] evaluated the impact of heteroatom doping composition and structural characteristics of carbon materials on the effectiveness of capacitance using ML models. A comprehensive dataset of 147 carbon-based supercapacitor sets was compiled from the existing literature.…”
Section: Capacitance Prediction With MLmentioning
confidence: 99%
“…Consequently, there has been a shift in focus towards using ML models to forecast the effectiveness of SCs, considering the impact of doping materials as a percentage, as well as other structural and operational characteristics. Mishra et al [101] evaluated the impact of heteroatom doping composition and structural characteristics of carbon materials on the effectiveness of capacitance using ML models. A comprehensive dataset of 147 carbon-based supercapacitor sets was compiled from the existing literature.…”
Section: Capacitance Prediction With MLmentioning
confidence: 99%
“…ML methods can also be used to find the relative importance of the supercapacitor characteristics to their capacitance behavior by applying sensitivity analysis methods such as SHAP or Sobol indices. It is often observed that the specific surface area (SSA), pore volume (PV), and oxygen ratio are among the most important parameters representing the properties of carbon electrodes. ,, The ML predictions offer valuable insights into the synthesis of better carbon materials, help to identify critical features, optimize reaction conditions, and predict and optimize the cycle life, thereby facilitating advancements in carbon material synthesis. ,, Conversely, new experimental data can be leveraged to refine and enhance the predictive accuracy of ML models.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanofillers, with their distinctive physical characteristics, are preferred for creating high-performance epoxy nanocomposites compared to other nanofillers [ 4 , 5 , 6 ]. These nanocomposites have garnered significant attention from both academic and industrial sectors due to their broad range of potential uses [ 7 , 8 , 9 ]. Furthermore, graphene and graphene oxide have emerged as promising candidates for a wide range of applications, such as communication, photodetectors, and chemical sensors [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%